Penggunaan Media Pembelajaran Wordwall dalam Meningkatkan Keaktifan Belajar Peserta Didik Pada Mata Pelajaran IPAS di Sekolah Dasar - Putri, Salsabila; Nandayani, Komang; Widiyanti, Ni Nyoman Sri; Supriyadi, Supriyadi; Hermawan, Jody Setya (Innovative: Journal Of Social Science Research, 2024)
The activeness of students during the learning process is important. Low learning activeness, especially IPAS learning, is a problem that must be considered by educators. The lack of innovation of educators in using learning media is one of the factors that students do not actively participate because students feel bored because learning feels less interesting. This study aims to analyze the learning activeness of students through the use of wordwall learning media in IPAS subjects in elementary schools. The research was conducted using qualitative research methods with the type of literature study research. The research process is carried out collecting several references that are in accordance with the topic that comes from journals and books related to the topic discussed. The author analyzes the various references to examine the use of wordwall in increasing the learning activeness of students in the scope of IPAS subjects in elementary schools. The results showed that the use of interactive game-based wordwall media can attract interest, increase motivation, and encourage the involvement of students to be more active in the learning process.